2003
DOI: 10.2337/diacare.26.4.1277
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Herbs and Dietary Supplements for Glycemic Control in Diabetes

Abstract: OBJECTIVE -To conduct a systematic review of the published literature on the efficacy and safety of herbal therapies and vitamin/mineral supplements for glucose control in patients with diabetes.RESEARCH DESIGN AND METHODS -We conducted an electronic literature search of MEDLINE, OLDMEDLINE, Cochrane Library Database, and HealthSTAR, from database inception to May 2002, in addition to performing hand searches and consulting with experts in the field. Available clinical studies published in the English language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
475
0
23

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 705 publications
(508 citation statements)
references
References 115 publications
10
475
0
23
Order By: Relevance
“…Antidiabetic activities of fenugreek and cinnamon were described before (Shane-Mc-Worther, 2001, Yeh et al, 2003, Khan et al, 2003; inhibitory effects on α-amylase activity were not detectable.…”
Section: Resultsmentioning
confidence: 99%
“…Antidiabetic activities of fenugreek and cinnamon were described before (Shane-Mc-Worther, 2001, Yeh et al, 2003, Khan et al, 2003; inhibitory effects on α-amylase activity were not detectable.…”
Section: Resultsmentioning
confidence: 99%
“…It is, however, unclear how chamomile use is associated with reduced mortality. Recent studies of chamomile showed potential benefits in treating hyperglycemia, diabetic complications (Kato et al, 2008;Yeh, Eisenberg, Kaptchuk, & Phillips, 2003) and anxiety disorder (Amsterdam et al, 2009). Other potential pathways include its cholesterol-lowering, antioxidant, and anti-platelet properties which may convey cardiovascular benefits; however, we did not observe a positive effect on cardiovascular disease mortality after controlling for other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble fibers, including pectins, gums, and mucilages, increase the viscosity of food in the gut, slowing or reducing sugar absorption. The effect of soluble fiber in reducing serum glucose concentrations is a proposed mechanism of action for the herbal hypoglycemic nopal (De Smet, 2002;Yeh et al, 2003). However, fiber content is not the sole mechanism of action, since fasting blood glucose levels are affected.…”
Section: Nopal (Opuntia Ficus Indica)mentioning
confidence: 99%
“…Although there is, as yet, little scientific evidence in support of its efficacy in these settings, a randomized trial has shown that topical aloe vera gel is superior to placebo in the treatment of plaque psoriasis (Syed et al, 1996). Preliminary evidence suggests that taking one tablespoon (15 mL) of aloe gel daily for 42 days can significantly decrease blood glucose levels in women with type 2 diabetes (Yeh et al, 2003). There is also some evidence that applying aloe extract 0.5% cream 3 times daily increases healing rates compared to aloe gel or placebo.…”
Section: Aloe (Aloe Vera)mentioning
confidence: 99%
See 1 more Smart Citation